(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2013)
The ring transformation reactions of 2-hetaryl-2-(tetrahydro-2-furanyliden)acetonitriles with guanidine as 1,3-N,N-binucleophiles have been investigated. The method allows obtaining diaminopyrimidines, which have been of great interest in recent years due to their potent biological and pharmacological properties.